Covid-19 accelerating the dynamics of Artificial Intelligence disruption - ALMIRALL, Esteve (Institutional Knowledge at Singapore Management University, 2021)
Covid-19 has probably been not only one of the largest social experiments ever, but also the trigger that unleashed the full potential of the ongoing digital transformations, overcoming social resistances to the technology that before seemed unsurmountable. Suddenly, remote work became the new normal, as did remote teaching. With it began a transformation of urban activity, the scope of which we have not yet even glimpsed.Traditionally, the debate around the impact of artificial intelligence revolved around two complementary but opposite views: augmentation and automation. Much work has been devoted to drawing the line between the two and estimating how many existing jobs are likely to be replaced, and how many will need to relearn new skills to cope with augmentation.However, a discourse focused on the factors that trigger this disruption and, in its consequences, leaves little room to understand the new dynamics that emerged and drive internal transformation in the structure of organizations and society itself. We will adopt this perspective to elucidate these dynamics and the new paths they are charting.